Obtenção e caracterização de cimentos sulfobelíticos sintetizados a partir do resíduo de bauxita - Fortes, Gustavo Mattos (Universidade Federal de São Carlos, 2013)
The modern society has an elevated and increasingly pattern of consumption, demanding a high industrial productivity and generating enormous residue volumes, resulting in a conduct that is becoming each time more unsustainable. The bauxite residue (BR), also known as red mud, is the residue of biggest generation by the aluminum industry, being stocked in large impermeable deposits, being this way the passive of the highest management cost for this industrial sector. Only in Brazil the minimum estimative of BR generation is of 10.7 million tons/year. Nevertheless, the BR, although alkaline, is composed by fine particles rich in iron, aluminum and silicon oxides, consisting therefore in a raw material of possible interests for many applications in traditional ceramics, mainly in civil construction. In this alternative, the use of BR, as a raw material, in the development of new sulfobelite cements for civil construction shows itself very attractive. These cements are characterized by the calcium sulfoaluminate phase (C4A3S), higher contents of belite (β-C2S) and calcium ferrialuminate (C4AF), as well as the absence of alite (C3S). Due to this composition these cements have been showing economic-environmental, and possibly even technical, advantages over Portland cement. From their benefits, highlights a reduction of 30% to 62% on equivalent CO2 emissions, as for less limestone used, as well as, lower burning temperature, bringing also energy reduction in the process. The sulfobelite clinker was synthesized using the raw materials: limestone, commercial gypsum, BR and São Simão clay. Using expressive BR content, up to 11.2wt%; understanding the influence of Al2O3/Fe2O3 (A/F) ratio; and gypsum additions; for the synthesis of sulfobelite cements it was possible to develop satisfactory formulations. These sulfobelite cement formulations presented apparent porosity and mechanical strength equivalent to commercial Portland cement (CPII-Z32 and CPV-ARI), else than the formation of hydration products similar to a commercial calcium sulfoaluminato cement.
Synthesis and characterization of sulfobelitic cements made with red mud abstract
Keywords: Cimento; Cimentos especiais; Cimentos sulfobelíticos; Lama vermelha; Resíduo de bauxita; Sulfoaluminato de cálcio; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA